1985
DOI: 10.1302/0301-620x.67b4.4030856
|View full text |Cite
|
Sign up to set email alerts
|

The results of early posterior release in resistant club feet. A long-term review

Abstract: Seventy resistant club feet in 46 patients were treated within the first six months of life by posterior release as an incident in continuing conservative care and were later assessed at an average age of 15 years. Assessment was made upon strict clinical criteria, including appearance, function and degree of pain during activity; the results were excellent in 22 feet, good in 19, and poor in 29. We also studied the correlation between the radiographs and the final outcome. From these data we propose certain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…To avoid these outcomes, early and even primary surgical treatment of clubfoot is practiced, often with equally disturbing failures and complications. 3,[9][10][11][12][13][14][15][16][17][18][19][20][21] Since the late 1940s we have followed the method of correction developed by the senior author (I.V.P.). 22,23 This method involves weekly stretching of the deformity followed by application of a long-leg cast.…”
mentioning
confidence: 99%
“…To avoid these outcomes, early and even primary surgical treatment of clubfoot is practiced, often with equally disturbing failures and complications. 3,[9][10][11][12][13][14][15][16][17][18][19][20][21] Since the late 1940s we have followed the method of correction developed by the senior author (I.V.P.). 22,23 This method involves weekly stretching of the deformity followed by application of a long-leg cast.…”
mentioning
confidence: 99%
“…Green and Lloyd-Roberts (23) found that the older the patients after 5 months of age, the worse the surgical outcome. Cummings and Lovell (24) stated that when surgery was performed before 2 months of age there was no improvement in outcome over a later age.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report that the best result for clubfoot surgery occur when surgery is performed at an early age (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital clubfoot deformity is a correctable deformity with good to excellent results if the treatment is instituted as soon as the deformity is recognized [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%